2019
DOI: 10.11591/ijpeds.v10.i2.pp1110-1122
|View full text |Cite
|
Sign up to set email alerts
|

Robust coordinated control using backstepping of flywheel energy storage system and DFIG for power smoothing in wind power plants

Abstract: <p>This paper presents a robust coordinated control of a flywheel energy storage system (FESS) and a doubly fed induction generator (DFIG) based wind energy conversion system (WECS), used to smooth the wind induced output power fluctuations. The overall system control combines field oriented control schemes and nonlinear backstepping approach applied first, to the machine side converter (MSC) to regulate the DFIG active and reactive power in order to ensure maximum power point tracking (MPPT) operation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In order to enhance system robustness, the proposed control strategy revolves around the backstepping control approach, which is a recursive and systematic control methodology used for nonlinear systems control, such that, the feedback control loop that guarantees the overall system stability and behavior can be efficiently elaborated. Figure 7 shows the block diagram of the proposed RtSC control [20].…”
Section: Control Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance system robustness, the proposed control strategy revolves around the backstepping control approach, which is a recursive and systematic control methodology used for nonlinear systems control, such that, the feedback control loop that guarantees the overall system stability and behavior can be efficiently elaborated. Figure 7 shows the block diagram of the proposed RtSC control [20].…”
Section: Control Objectivesmentioning
confidence: 99%
“…It can be observed that the current waveforms have also been modified due to the addition of the two sinusoidal components with different frequencies. Unlike the stator overcurrent, which can be tolerated by the machine thermal capacity, the overcurrent in the rotor terminals could damage the power electronic interfaces, normally designed to carry only around one-third of the generator rated power [20]. Figure 12 shows the overvoltage induced at the DC bus capacitor during the fault.…”
Section: Simulationswithout the Proposed Control Strategymentioning
confidence: 99%
“…The justification for selecting these three algorithms is due to their wide applicability and readily to be implemented in Matlab. These algorithms also have been proven to deliver good optimization accuracy, particularly in battery storage application in renewable energy sources [7,12,13,[21][22][23].…”
Section: Optimization Of Battery Parametersmentioning
confidence: 99%
“…Passivity-based control provides robust controllers that have a clear physical interpretation in terms of the system's interconnections with its environment. In particular, the total energy of the closed-loop system is the difference between the energy of the system and the energy supplied by the controller [7]. Moreover, since the Euler-Lagrange structure is preserved in a closed loop, the passivity control has a robust stability with respect to the non-modelled dissipative effects and exhibits robust performances due to its inverse optimality [8,9].…”
Section: Introductionmentioning
confidence: 99%